FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SEDIAAN FACE MIST FRAKSI DAUN LIDAH MERTUA (Sansevieria trifasciata Prain) - Yuniarsih, Nia; farhamzah, Farhamzah; Wulansari, Nur Intan (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Face mist is a cosmetic that is often used as a skin freshener, serves to refresh facial skin by removing residual oil, as a mild disinfectant, while closing pores again and can have activity as an antioxidant. The Sansevieria trifasciata Prain contains flavonoids, alkaloids and tannins that have the potential to be a source of natural antioxidants. This study aims to examine the potential of n-hexane, ethyl acetate and water fractions of Sansevieria trifasciata Prain as active substances in face mist formulations. This study used the Fractionation and DPPH methods to determine the effectiveness of antioxidant activity of various formulations with F1 (n-hexane fraction); F2 (ethyl acetate fraction) and F3 (water fraction), which were compared with commercial products.. The results showed that F1 and F2 had strong antioxidant activity, while F3 had moderate antioxidant activity. The results of physical evaluation and stability tests using the accelerated stability method (cycling test) showed that the resulting face mist preparation met SNI standards, had good stability and did not cause irritation. From these results, it can be concluded that the n-hexane, ethyl acetate and Sansevieria trifasciata Prain leaf water fractions have the potential to be effective natural antioxidants in the formulation of face mist preparations.